Variabilidade clínica e genética na lipodistrofia parcial familiar - Veras, Victor Resende (2023)
Lipodystrophies are rare conditions characterized by partial or total loss of subcutaneous adipose tissue. The lack of metabolically active adipose tissue can lead to ectopic fat accumulation and insulin resistance. Familial partial lipodystrophy (FPLD) is a disease with wide clinical and genetic variation, with 7 described subtypes and estimated prevalence of 1.67 cases/million. This cross-sectional study analyzed 42 FPLD patients in Ceará, aiming to compare the clinical characteristics of FPLD patients followed at the Endocrinology and Diabetes Service of the Walter Cantídio University Hospital. The main inclusion criterion was a previous clinical or genotypic diagnosis of FPLD. The individuals were differentiated into three groups according to genetic study and/or clinical-anthropometric characteristics. Those with positive genetic mutation for genes known to be related to FPLD were considered FPLD+ group. Those who had negative genetic testing but met the Köb index criteria were classified as subtype 1 (FPLD1). Patients who had clinical and anthropometric criteria for FPLD but negative genotyping and negative Köb index were classified as FPLDX. For comparison of anthropometric data, a healthy control group matched for age, sex, and body mass index in a 2:1 ratio was selected. Data were collected through medical record review after signing informed consent. Sociodemographic, anthropometric, clinical, laboratory, and densitometry data of these patients were analyzed. Pearson's chi-square test and Fisher's exact test were used for association between categorical variables. A significance level of 5% was adopted. Unlike what is described in the literature, the LMNA mutation in codon 582 was the most common. Among the main diagnostic parameters of FPLD, a statistical correlation was observed between all groups for Köb index, thigh skinfold thickness (TS), and fat mass ratio. A cutoff point of 20mm for TS in FPL women was found, which is lower than the value classically described in the literature for the diagnosis of FPLD. This may be a more suitable value for women in northeastern Brazil. Good correspondence was observed between leg fat percentage (LFP) by densitometry and TS as diagnostic support tools in FPLD. LFP < 29.6% appears to be a useful tool to aid in the diagnosis of these women. A high prevalence of diabetes (83%), hypertriglyceridemia (85%), hepatic steatosis (62.5%), coronary artery disease (17%), and other complications, including in eutrophic patients, was observed. This study proposes a new clinical classification for FPLD with negative genotype, differentiating them into two subtypes: FPLD1 and FPLDX. The separation of these groups helps to understand that knowledge about the genetic basis of this disease is constantly evolving. It is expected that there will be new subgroups to be defined within the FPLDX population. Despite being rare, FPLD is an important model for studying the relationship between adipose tissue, tissue biology, and susceptibility to metabolic diseases.